Efektivitas Peran Humas dan Sistem CRM dalam Meningkatkan Kepuasan Pengguna Jasa Kepelabuhanan - Rachim, Rossa Rikha Putri; Qadrifa, Sabrina Sofi (UMSU, 2025)
Customer satisfaction plays a vital role in assessing the quality of a service. A service is considered successful when it meets the needs and expectations of its users. Therefore, measuring customer satisfaction is essential to delivering services that are more effective, efficient, and responsive. One of the key challenges is maintaining a customer-oriented service focus. This study aims to examine the role of Public Relations at the Pelindo Bengkulu Branch in enhancing service satisfaction, exploring the communication media used to foster customer engagement, and identifying communication-related challenges. The research applies a qualitative descriptive approach, gathering data through observations, questionnaires, and institutional documentation. The findings show that Pelindo Bengkulu has implemented several initiatives to improve customer satisfaction, including a direct-contact Customer Care line and the strategic use of Instagram as a platform for delivering information and building relationships with customers.